Characterization of impurities in cefpodoxime proxetil using LC-MSn - Jin Li; Dousheng Zhang; Changqin Hu (Elsevier, 2014)
Reversed-phase liquid chromatography coupled with electrospray ionization tandem mass spectrometry (ESI-MS/MS) was used to characterize impurities in cefpodoxime proxetil, an ester-modified prodrug. Based on the mechanisms by which cephalosporins are degraded, stress tests were designed and performed. The bulk material and capsule were eluted through a C18 column with formic acid-methanol-water as the mobile phase. In total, 15 impurities were characterized in commercial samples, including 7 known impurities and 8 new impurities. The structures of these unknown compounds were deduced via comparison with the fragmentation patterns of cefpodoxime proxetil. Data from this systematic study will help improve the safety and quality of cefpodoxime proxetil.